A Qualitative Exploratory Study of the Knowledge, Forensic, and Legal Challenges from the Perspective of Police Cybercrime Specialists. (29th July 2020) - De Paoli, Stefano; Johnstone, Jason; Coull, Natalie; Ferguson, Ian; Sinclair, Georgina; Tomkins, Patrick; Brown, Maureen; Martin, Rebecca
Abstract: The extant literature has demonstrated that there is a need for more empirical research on the subject of policing cybercrime. This article makes a contribution and offers a qualitative exploration of the problem of policing cybercrime from an international perspective. It structures the analysis around three main challenges: the knowledge, forensic, and legal challenges. A literature review supports the evidence that these issues are core challenges when policing cybercrime. Through 13 semi-structured interviews with cybercrime specialists from 8 countries, these three challenges are further investigated. A thematic analysis of the interviews, whilst confirming some of the previous literature findings, also outlines novel findings. Interview analysis shows that in some areas little recent progress has been made, in particular the recording of cybercrime. However, in other areas new creative solutions have been implemented, including filling the policing skills gap with civilian specialists. The article concludes by offering recommendations for addressing some of the challenges for policing cybercrime.